Why is the Hong Kong housing market unaffordable? Some stylized facts and estimations - Charles Ka Yui Leung; Joe Cho Yiu Ng; Edward Chi Ho Tang (Osaka University, Institute of Social and Economic Research (ISER), 2020)
The house price in Hong Kong is well-known to be "unaffordable." This paper argues that the commonly used house price-to-income ratio may be misleading in an economy with almost half of the population living in either public rental housing or subsidized ownership. Moreover, we re-focus on the relationships between economic fundamentals and the housing market of Hong Kong. While the aggregate GDP, population, longevity continues to grow, the real wage and household income fall behind. The trend component of the real GDP growth suffers a permanent downward shift after the first quarter of 1989 (a "political scar"). The trend component of real wage growth is close to zero, and the counterpart of real consumption and real investment decline steadily. Meanwhile, the trend component of the real housing rent and price display patterns that decouple from the macroeconomic variables. We also discuss the directions for future research.
Keywords: E20; J01; R00; 330; housing demand; migration; structural break; time series decomposition; wage index andhousehold income